Faculty members’ strategies to foster students’ learning engagement in writing class - Nurmalinda Maharani Farizka; Bambang Yudi Cahyono (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2021)
Fostering students' learning engagement plays a crucial role in higher education institutions. It is essential to assist students' learning best, satisfaction, and preferred faculty members' teaching strategies. The purpose of this study was to find out the faculty members' strategies by mapping out the students' perceptions of their experiences in writing classes with highly-engaging environments. Thirty participants from undergraduate students of English Language Teaching (ELT) at five state universities in Malang, Indonesia were selected purposively. All participants identified themselves as active students as they already had sophisticated results in the writing classes. Hence, the researchers employed a Likert scale questionnaire and semi-structured interview guide in collecting the data. The study revealed that the learning management system, materials, discussion, and feedback sections were rated highly as the most common activities during the teaching and learning of writing skills. Almost all of the participants mentioned confidently that those fundamental activities that boosted their participation resulted in positive learning engagement. Specifically, the researchers found that the faculty members' indirect learning strategy that specified only on the social learning strategies can foster students' engagement well. In highlight, this study offers teaching reflections by spotlighting various engagement strategies implemented in the writing class circumstances.